2011
DOI: 10.1007/s00415-011-6062-5
|View full text |Cite|
|
Sign up to set email alerts
|

A systematic review of quality of life in adults with muscle disease

Abstract: We reviewed the literature on how muscle disease affects quality of life compared to healthy controls, and the factors that influence the effects of muscle disease on quality of life. We also wanted to know whether quality of life differed between muscle diseases. We searched online databases and identified 26 relevant studies. The quality of each study was assessed, results sections analysed and a database of factors associated with quality of life developed. We graded the level of evidence supporting the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
126
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(141 citation statements)
references
References 50 publications
13
126
1
1
Order By: Relevance
“…However, DM1 patients did not differ from the reference population with regard to the MCS, in accordance with previous findings [31]. In their systematic review of QoL in muscle diseases, Graham et al [32] emphasized that the mental domains of QoL measures are not as consistently affected by having muscle diseases than physical domains. The counterintuitive preservation of high scores on mental or psychosocial indices in chronic illness has been explained by the fact that patients' limitations in activities of daily living develop over a long period of time.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…However, DM1 patients did not differ from the reference population with regard to the MCS, in accordance with previous findings [31]. In their systematic review of QoL in muscle diseases, Graham et al [32] emphasized that the mental domains of QoL measures are not as consistently affected by having muscle diseases than physical domains. The counterintuitive preservation of high scores on mental or psychosocial indices in chronic illness has been explained by the fact that patients' limitations in activities of daily living develop over a long period of time.…”
Section: Discussionsupporting
confidence: 76%
“…The factors with the greatest empirical support to date that may affect QoL in populations affected by muscle diseases include disease severity, mood, pain, and fatigue [32]. In the present study, these factors were identified as significant correlates of reduced QoL except for pain.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The impact for the affected person and their families can be devastating, particularly because muscular dystrophy can be of early onset [5,6]. Consequently, it remains important to have accurate prevalence rates to ensure that people affected by muscular dystrophies receive the support they need.…”
Section: Discussionmentioning
confidence: 99%
“…In myotonic dystrophy not only are muscle weakness and myotonia clinical features, but nearly every system including the endocrine system is affected [4]. Across the muscular dystrophies, symptoms commonly lead to difficulties with physical activity including walking and functioning in every-day life, reducing quality of life and placing a high strain on both the individuals and their families [5,6]. …”
Section: Introductionmentioning
confidence: 99%